Application of Zachman Framework in Designing Enterprise Architecture of Setunggal Coffee Business - Pratama, Alvin Putra; Santoso, Maulana Arif; Pakaja, Fachrudin (International Journal of Multidisciplinary Applied and Science Research, 2025)
This research aims to design enterprise architecture in Setunggal Coffee business using Zachman Framework as a structural and comprehensive approach. In facing the challenges of digitization and information management, this coffee business needs an integrated information system that suits its organizational needs. This research uses a qualitative method with a case study approach. Data collection techniques were conducted through direct observation, interviews with business owners, and documentation studies of operational processes. The results showed that the Zachman Framework is able to map all business elements from various perspectives, from planners to system implementers. With this approach, information needs and business processes can be described more clearly and structured. The resulting architecture design is able to support decision-making, strengthen coordination between business units, and improve operational efficiency. The implications of this research provide a strong basis for the development of enterprise architecture-based information systems at the scale of small and medium enterprises (SMEs). In addition, this approach can also be used as a reference for other businesses in building digital systems that are adaptive, flexible, and aligned with business goals.